The effect of Polygonum minus extract on cognitive and psychosocial parameters according to mood status among middle-aged women: a randomized, double-blind, placebo-controlled study [Retraction] - Shahar S; Aziz AF; Ismail SNA; Yahya HM; Che Din N; Abdul Manaf Z; Badrasawi M (Clinical Interventions in Aging, 2017)
Shahar S, Aziz AF, Ismail SNA, et al. The effect of Polygonum minus extract on cognitive and psychosocial parameters according to mood status among middle-aged women: a randomized, double-blind, placebo-controlled study. Clin Interv Aging. 2015;10:1505–1520.This article has been retracted at the request of the Editor-in-Chief of Clinical Interventions in Aging. It was brought to the attention of the Editorial team by the authors that there were a number of reporting errors in the Methods, Results and Figures 3–5. Due to the extent of the inaccuracies, the scientific validity of the data, and hence the conclusions, are questionable.This retraction relates to